The association between chronic pain and pre-and-post migration experiences in resettled humanitarian refugee women residing in Australia - Areni Altun; Sze-Ee Soh; Helen Brown; Grant Russell (BMC, 2022)
Abstract Background Refugee women are potentially at increased risk for chronic pain due to circumstances both in the pre-migration and post-settlement setting. However, this relationship between refugee-related challenges introduced along their migration trajectories and chronic pain remains unclear. This study will therefore examine the association between pre- and post-migration factors and chronic pain in refugee women five years into resettlement in Australia. Methods The first five waves of data from the 'Building a New Life in Australia' longitudinal study of humanitarian refugees living in Australia was analysed using logistic regression models to investigate the association between predictor variables and chronic pain. The study outcome was chronic pain and predictors were migration process and resettlement factors in both the pre-and post-settlement setting. Results Chronic pain was reported in 45% (n = 139) of women, and among these a further 66% (n = 120) also reported having a long-term disability or health condition that had lasted 12 months. Pre- migration factors such as increasing age (OR 1.08; 95% CI 1.05, 1.11) and women who migrated under the Women at Risk Visa category (OR 2.40; 95% CI 1.26, 4.56) had greater odds of experiencing chronic pain. Interestingly, post migration factors such as women with better general health (OR 0.04; 95% CI 0.01, 0.11) or those who settled within metropolitan cities (OR 0.29; 95% CI 0.13, 0.68) had lower odds of experiencing chronic pain, and those who experience discrimination (OR 11.23; 95% CI 1.76, 71.51) had greater odds of experiencing chronic pain. Conclusion Our results show that there is a high prevalence of chronic pain in refugee women across the initial years of resettlement in Australia. This may be in part due to pre-migration factors such as age and migration pathway, but more significantly the post migration context that these women settle into such as rurality of settlement, poorer general health and perceived discriminatory experiences. These findings suggest that there may be many unmet health needs which are compounded by the challenges of resettlement in a new society, highlighting the need for increased clinical awareness to help inform refugee health care and settlement service providers managing chronic pain.